PENYELESAIAN PERKARA PIDANA DI LUAR PENGADILAN OLEH KEJAKSAAN DALAM MEWUJUDKAN TUJUAN PENEGAKAN HUKUM - Satya Wirawan (2022)
Abstract One of the state apparatuses who are given the task and authority to carry out law enforcement is the Prosecutor. In carrying out their duties and functions, prosecutors are organized in an institution called the Prosecutor's Office of the Republic of Indonesia or can be called the Prosecutor's Office. The main task of the Prosecutor's Office carried out by the Prosecutor is to prosecute criminal cases. In carrying out the task of prosecution, the Prosecutor is given the authority to determine whether or not a case can be submitted to the court and what articles will be indicted. The authority of the Prosecutor in carrying out the settlement of criminal cases outside the court which makes the author more tendentious for research. The problems of this research are 1). What are the obstacles to solving criminal cases outside the court by the Prosecutor's Office? 2). How is the settlement of cases outside the Court carried out by the Prosecutor's Office to be in accordance with the values of justice? By using the type of normative juridical research, it is known that: The authority of the Prosecutor's Office in resolving criminal cases outside the Court can realize the objectives of law enforcement, namely justice, legal certainty and benefit for the community. The settlement of criminal cases outside the court can also realize the ideals of a fast, simple and inexpensive judiciary and optimize the participation of the community in law enforcement. Keywords: Prosecutor's Office, Settlement of Criminal Cases Outside Court, Diversion, Restorative Justice, Restorative Justice.